A psychoanalytic approach to treating psychosis genesis, psychopathology and case study - De Masi, Franco (Routledge, 2020)
"This ground-breaking examination begins by clearly explaining complex terms and theories from the most significant thinkers in psychoanalysis. Split into 3 parts, it then explores the problems faced when following one specific technique for understanding the psychotic process. Practical as well as theoretical, Part 2 illustrates how to prepare an appropriate setting for the patient, including the importance of listening and the analyst's approach, as well as highlighting key features of the condition, such as delusions, hallucinations, infantile withdrawal and psychotic dreams. Acknowledging that psychosis is a psychic transformation which the mind works as a sensorial organ, the author asserts that the seeds are sown in childhood through emotional trauma, leading to withdrawal in a fantasy world"--